On decay constants and orbital distance to the Sun—part I: alpha decay. (28th November 2016) - Pommé, S; Stroh, H; Paepen, J; Van Ammel, R; Marouli, M; Altzitzoglou, T; Hult, M; Kossert, K; Nähle, O; Schrader, H; Juget, F; Bailat, C; et al.
Abstract: Claims that proximity to the Sun causes variation of decay constants at permille level have been investigated for alpha decaying nuclides. Repeated decay rate measurements of 209 Po, 226 Ra, 228 Th, 230 U, and 241 Am sources were performed over periods of 200 d up to two decades at various nuclear metrology institutes around the globe. Residuals from the exponential decay curves were inspected for annual oscillations. Systematic deviations from a purely exponential decay curve differ in amplitude and phase from one data set to another and appear attributable to instabilities in the instrumentation and measurement conditions. The most stable activity measurements of α decaying sources set an upper limit between 0.0006% and 0.006% to the amplitude of annual oscillations in the decay rate. There are no apparent indications for systematic oscillations at a level of weeks or months. Oscillations in phase with Earth's orbital distance to the sun could not be observed within 10 −5 –10 −6 range precision.